Analysis of the effect of initial hemostasis resuscitation with recombinant human coagulation factor VII a on the treatment of postoperative hemorrhage in cardiac surgery - Yan Yu; Maomao Liu; Xuran Lu; Li Yu; Nan Liu (Journal of Cardiothoracic Surgery)
Abstract Objective To investigate the effectiveness of initial hemostatic resuscitation(IHR) on the treatment of bleeding with recombinant human coagulation factor VIIa after cardiac surgery. Methods The clinical data of patients who received rFVIIa hemostatic treatment after cardiac surgery at Beijing Anzhen Hospital, Capital Medical University, from January 1, 2021, to December 31, 2021 were retrospectively collected. A total of 152 cases were included in the study. In this study, initial hemostatic resuscitation was defined as a platelet count > 50,000 per µL and fibrinogen > 1.5 g/L when rFVIIa was used. Based on whether initial hemostatic resuscitation was completed during the application of rFVIIa, patients were divided into an initial hemostatic resuscitation group and an un-initial hemostatic resuscitation group. Baseline information, medical history, surgery-related data, postoperative bleeding volume, transfusion product volume, and overall mortality data were collected for each patient, and the postoperative bleeding volume, transfusion volume, and overall mortality rate were compared between the two groups, thus evaluating the effectiveness of initial hemostatic resuscitation on the treatment of postoperative bleeding with recombinant human coagulation factor VIIa in cardiac surgery. Result In this study, patients in the initial hemostasis resuscitation group received a lower dose of recombinant activated factor VII (rFVIIa) [29.41 (26.23, 34.63) µg/kg vs. 36.04 (28.57, 59.27) µg/kg, P = 0.002], had lower blood product requirements [41 (40.2%) vs. 31 (62%), P = 0.011], received fewer units of packed red blood cells within 24 h postoperatively [0 (0, 2) U vs. 2 (0, 6) U, P = 0.018], had a lower volume of plasma transfusion [0 (0, 0) ml vs. 0 (0, 400) ml, P = 0.021], exhibited a lower peak value of D-dimer after surgery [756 (415.5, 2140.5) ng/ml vs. 1742.5 (675.25, 3392) ng/ml, P = 0.003], experienced fewer postoperative neurological complications [4 (3.92%) vs. 12 (24%), P < 0.001], had a lower mortality rate [8 (7.84%) vs. 14 (28%), P = 0.001], and had a shorter duration of mechanical ventilation [17 (12, 60.13) hours vs. 39.5 (15.75, 115.13) hours, P = 0.022]. Conclusion Initial hemostasis resuscitation can significantly reduce the bleeding volume and blood product requirements in patients with bleeding complications after cardiac surgery who were treated with rFVIIa, thus improving patient prognosis. And it is crucial to closely monitor for symptoms and signs of thromboembolic complications during the application of rFVIIa.